A prospective randomized study that compares three different dressings for the prevention of surgical site infections following major heart surgery - María Jesús Pérez-Granda; Gregorio Cuerpo; José María Barrio; Maricela Valerio; Patricia Muñoz; Ángel González Pinto; Dominique Encarnación Valencia; Félix Sánchez Vicario; Emilio Bouza; Cardiovascular Infection Study Group (Scientific Reports)
Abstract Surgical site infection (SSI) is among the most common complication of major heart surgery patients with incidences ranging from 0.5 to 16.5%. Our aim was to compare the incidence, etiology and prognosis of surgical wound infection in three groups of patients with three different type of wound dressing used in a large cohort of patients undergoing cardiac surgery requiring median sternotomy (MHS). This was a randomized, prospective clinical study conducted in 900 adults undergoing MHS at our center from October 10, 2019 to February 22, 2022. Before surgical closure, patients were randomized to 3 different wound dressing groups (300 patients per group): A) conventional gauze (Mepore®), B) Absorbent: polyurethane foam (Mepilex®), or C) Vacuum-negative-pressure therapy (NPWT) wound dressing (PICO®, Smith & Nephew S.A.). Overall, 900 patients were randomized as follows: 300 patients in each group received conventional, absorbent or vacuum wound dressing respectively. Rates of SSI in groups A, B and C were respectively 2.3%, 3% and 3% for superficial SSI (sSSI) (p = 0.848) and 2%, 2% and 0.7% for postsurgical mediastinitis (PSM) (p = 0.313). Mortality in the whole group was 4.4% there being no significant differences between the three groups (4.7%, 5.7% and 3% respectively; p = 0.277). The NPWT system was better at preventing PSM than the other dressings only in the subgroup of patients undergoing coronary artery bypass graft surgery (CABG) with mammary artery grafts. We have not been able to demonstrate significant differences in the incidence of SSI in the whole series with any of the different dressings. The newer, more expensive, NPWT dressing were more effective only at preventing Post-Surgical Mediastinitis in patients undergoing CABG with internal mammary artery grafts. ClinicalTrials.gov identifier (NCT number): NCT03905213